Functional foods and dietary supplements in the management of non-alcoholic fatty liver disease: A systematic review and meta-analysis - Wang, Lei-lei; Zhang, Pian-hong; Yan, Hui-hui (Frontiers in Nutrition, 2023)
Objective: In this systematic review and meta-analysis, we aimed to clarify the overall effects of functional foods and dietary supplements in Nonalcoholic Fatty Liver Disease (NAFLD) patients. Methods: Randomized controlled trials (RCTs) published in PubMed, ISI web of science, Cochrane library, and Embase from their inception until January 2022 were systematically searched to assess the effects of functional foods and dietary sup-plements in patients with NAFLD. The primary outcomes were liver-related measures, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), hepatic fibro-sis, and hepatic steatosis, while the secondary outcomes included body mass index(BMI), weight circumference (WC), triacylglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). The risk of bias in all studies was assessed with guidance provided in the Cochrane Hand-book for Systematic Reviews of Interventions. The study quality was evaluated using the Jadad scale. Random-effects or fixed-effects models were used to estimate mean differ-ence (MD). Results: Twenty-nine articles investigating functional foods and dietary sup-plements (antioxidants (phytonutrients and coenzyme Q10) =18, probiot-ics/symbiotics/prebiotics = 6, fatty acids = 3, vitamin D = 1, whole grain = 1) met the eligi-bility criteria. Our results showed that antioxidants could significantly reduce WC, ALT, AST, and LDL increases in patients with NAFLD but had no effect on BMI, TG, and TC. Probiotics/symbiotics/prebiotics could decrease BMI, ALT, and AST levels but did not have beneficial effects on serum lipid levels compared to the control group. Moreover, the efficacy of fatty acids for NAFLD was full of discrepancies. Additionally, vitamin D had no significant effect on BMI, liver transaminase, and serum lipids, while whole grain could reduce ALT and AST but did not affect serum lipid levels. Conclusion: The current study suggests that antioxidant and probiotic/symbiotics/prebiotic supplements may be a possible curative option in patients with NAFLD. However, the usage of fatty acids, vitamin D, and whole grain in clinical treatment is uncertain. Further exploration of the efficacy ranks of functional foods and dietary supplements is needed to provide a relia-ble basis for clinical application.